Hand surgery tricks of the trade - Beredjiklian, Pedro K. (Thieme Publishers, 2020)
"Hand surgery requires precision, in-depth expertise, and versatility in order to perform a wide variety of operations on fractures, tendon and nerve conditions, soft tissue injuries, rheumatoid deformities, and congenital defects. Hand Surgery: Tricks of the Trade by renowned Rothman Orthopaedic Institute hand surgeon Pedro K. Beredjiklian and an impressive group of contributors provides a clear roadmap on how to perform common hand surgery procedures. Concise step-by-step text enables readers to quickly read through, review, and understand the most salient points for each approach. Organized into 14 major sections and 88 chapters, this book encompasses the entire spectrum of orthopedic surgery procedures on the tendons, nerves, bones, and joints of the hand. The text starts with two sections focused on tendon repair and reconstruction. Subsequent sections detail open and endoscopic release and decompression techniques for nerve conditions, fixation and plating of hand and wrist fractures, osteotomy for bone reconstruction, arthroplasty for arthritis, and ligament repair for instability. The last four sections discuss plastic surgery procedures, including the use of diverse skin grafts and flaps, Dupuytren's disease, arthroscopy, and infections"--